Women’s Rights: A Study of Iran & Tunisia - Gorman, Meghan (Colloquium: The Political Science Journal of Boston College, 2019)
What factor is the most important determinant of a successful expansion of women’s rights? Through my research, I have concluded that societal norms are the most crucial factors inthe expansion of women’s rights. As a reflection of collective attitudes and expectations,norms determine how willing a society is to adopt new ideas about women’s rights andgender parity. However, these norms and expectations must be a genuine reflection ofpublic sentiment and not simply imposed on an unwilling population. The two cases I have examined in this essay are the Iranian Revolution of 1979 and Tunisia’s Jasmine Revolution of 2011. These cases have different outcomes: Tunisia experienced an expansion of women’s rights while a retraction of those rights occurred in Iran. Both cases prove that women’s rights are only expanded when a society believes that they align with its values and supports their integration.